A Highly Stretchable and Self‐Healing Composite Binder Based on the Hydrogen‐Bond Network for Silicon Anodes in High‐Energy‐Density Lithium‐Ion Batteries. Issue 12 (20th June 2022) - Luo, Peng; Lai, Pengyuan; Huang, Yiwu; Yuan, Yuan; Wen, Jianwu; Xie, Changqiong; Li, Jing; Liu, Lili
Abstract: Owing to its large theoretical capacity, silicon (Si)‐based materials are considered the most promising anode materials for high‐energy lithium‐ion batteries. However, the inherent huge volume change of silicon particles causes degradation of structural integrity and the rapid decay of electrode capacity, which severely restricts the practical application of Si‐based anodes. To alleviate the volume expansion, a novel self‐healing polymer binder based on the hydrogen bond complexation between polyacrylic acid (PAA) and polyethylene glycol (PEO) was prepared by a simple and environmentally friendly method. The PAA‐PEO composites binder can effectively improve the bulk effect of silicon and produce a more stable solid‐liquid interface film during long‐term cycling. The reversible specific capacity of the silicon anode using composite binder after 200 cycles at 0.5 C high current density is 870 mAh/g, which is 4.5 times higher than the remaining specific capacity of silicon anode using PAA as a binder. Abstract : Bound to get better : A self‐healing polymer binder based on the hydrogen bond complexation between polyacrylic acid (PAA) and polyethylene glycol (PEO) is prepared by a simple and environmentally friendly method. The PAA‐PEO composites binder can effectively improve the bulk effect of silicon and produce a more stable solid‐liquid interface film during long‐term cycling.